Effects of Life History and Brain Size on Cognition and Behavior: Studies on Prey-searching in the Spider Pholcus Phalangioides - (:unkn) unknown (My University, 2018)
There is tremendous diversity in body size across animals, including many examples of derived miniaturization. A reduction in body size is accompanied by a reduction in brain size, which is predicted to lead to limitations in cognition, but we have yet to find empirical evidence indicating what these limitations might be. I used a behavioral assay common in web spiders to explore this topic. I observed spiders as they searched for prey that they recently captured and lost. This assay has the advantage of being easily quantifiable while reflecting a spider’s evaluation and memory of lost prey. I conducted a series of experiments with the cellar spider, Pholcus phalangioides, using natural variation in body size between juveniles and adults. This allowed me to study effects of brain size on memory content and memory duration without potential confounding effects of cross-species differences in behavior. At the same time, it required a strong understanding of how behavior naturally changes with maturity. Therefore, I began by studying ontogenetic change in this behavior in order to better understand the patterns of change and their causes. In a comparison across age groups, from naïve spiderlings to mature adults, I found that even the youngest, smallest, least experienced spiders were capable of remembering and searching for prey (suggesting a lack of size-based limitations to memory content), and of all the age groups, they were the ones most motivated to recover lost prey. With these results in mind, I turned my attention to the question of memory duration. I ran an experiment in which I imposed a gap of time between memory formation and memory use. I found that although the smallest spiders had been the most motivated to recover prey, they were also the ones most negatively affected by a delay in the onset of searching. This points to either a higher rate of memory decay or a greater susceptibility to distraction in small brains. These results are among the first findings of size-based limitations to cognition, and they reveal specific ecological and evolutionary challenges faced by miniature animals.
Keywords: behvioral ontogeny; limitations; miniaturization; motivation